Alterations in urinary metabolomic profiles due to lead exposure from a lead–acid battery recycling site. (November 2018) - Eguchi, Akifumi; Nomiyama, Kei; Sakurai, Kenichi; Kim Trang, Pham Thi; Viet, Pham Hung; Takahashi, Shin; Iwata, Hisato; Tanabe, Shinsuke; Todaka, Emiko; Mori, Chisato
Abstract: Lead poisoning is considered a public health threat, particularly in developing countries. Health problems from Pb exposure occur in many parts of the world, especially near Pb mines, Pb smelters, and used lead–acid battery (ULAB) recycling plants. In this study, we analyzed the urine metabolome of residents in a village located near a ULAB recycling facility to investigate the biological effects of Pb exposure (ULAB: n  = 44, Reference: n  = 51). Lasso linear regression models were moderately predictive of blood Pb levels, as evaluated by a training set (R 2  = 0.813) and against an external test set (R 2 EXT  = 0.647). In lasso logistic regression models, areas under receiver operating characteristic curves, as measured by 5-fold cross-validation (AUCCV  = 0.871) and against an external test set (AUCEXT  = 0.917), indicated accurate classification of urine samples from the affected village and from a reference site. Ten candidate biomarkers identified at false discovery rates of <0.05 were associated with ATP-binding cassette (ABC) transporters, possibly related to the disruption of small-molecule transport in the kidney; amino acid, porphyrin, and chlorophyll metabolism; and the heme biosynthetic pathway. Collectively, the results suggest that lead Pb is related to the health effects in individuals residing in ULAB site by alteration of these biological pathways. Graphical abstract: Image 1 Highlights: The biological pathways related to blood Pb level in ULAB site were determined. Blood Pb levels were significantly higher in ULAB site. Urinary metabolome profiles in ULAB and reference site were significantly different. Pb exposure might be altered small molecular transportation and heme biosynthetic.